Students Designing ICT Support for Collaborative Learning in Practice - Nyvang, Tom; Tolsby, Haakon (Proceedings of the International Conference on Networked Learning, 2004)
The aim of this paper is to present an understanding of student practice and needs in relation to ICT-based support for Problem Oriented Project Pedagogy (POPP). The paper combines a theoretical understanding of POPP and results from a case study. An important characteristic of the students in the case study is that they construct and reconstruct a learning environment of their own choice without intervention from other parties. The paper identifies coordination of activities, coordination of knowledge construction and creation of joint images of experiences as key activities that may very well be supported by ICT. It is also clear from the case study that students demand a flexible tool that can be altered as the project progresses and needs emerge.